Risks of the Female Youth to Drugs and Substance Abuse in Makindu Town, Kenya - Jagero, Nelson; Mbulwa, Faith (Richtmann Publishing, 2012)
This study paid particular attention to investigating the nature and magnitude of risks exposed to the female youthabusing drugs in Makindu town Kenya. Consequently, this exploratory study had the following objectives: to identify and classifythe type of risks experienced by female youth exposed to drug and substance use. The research design used in the study wascase study design. Using snow ball sampling technique. 29 respondents were sampled for the study. The data was collected byuse of unstructured interviews designed for female youth abusing drug and substance, focus group discussion guides for femaleyouth whose partners abused drugs, key informant for key informants, participant observation and where possible anobservation checklist. According to the finding of the study, it was evident that: Biological risks included: lung complications,HIV/Aids, poor duty performance, falling , chipping and staining of teeth etc, social risks included; neglect of children, fightingwith spouse and others, influencing children to abuse sleeping pills etc, and psychological: loss of memory, mental illness,anorexia etc were cited to be some of the risks the female youth experienced after abusing drugs and substance.